2010
DOI: 10.1016/j.watres.2010.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Large scale analysis of virulence genes in Escherichia coli strains isolated from Avalon Bay, CA

Abstract: Contamination of recreational waters with E. coli and Enterococcus sp. is a widespread problem resulting in beach closures and loss of recreational activity. While E. coli is frequently used as an indicator of fecal contamination, and has been extensively measured in waterways, few studies have examined the presence of potentially pathogenic E. coli strains in beach waters. In this study, a combination of high-throughput, robot-assisted colony hybridization and PCR-based analyses were used to determine the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 57 publications
6
45
0
5
Order By: Relevance
“…Typical EPEC strains carry the LEE pathogenicity island, which encodes for several virulence factors, including intimin (eaeA) and the plasmid encoded bundle forming pilus (bfp) which mediates adhesion to intestinal epithelial cells (Kaper et al, 2004;Hamilton et al, 2010). In this study, the bfp gene was not detected along with eaeA in any of isolates.…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 58%
See 2 more Smart Citations
“…Typical EPEC strains carry the LEE pathogenicity island, which encodes for several virulence factors, including intimin (eaeA) and the plasmid encoded bundle forming pilus (bfp) which mediates adhesion to intestinal epithelial cells (Kaper et al, 2004;Hamilton et al, 2010). In this study, the bfp gene was not detected along with eaeA in any of isolates.…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 58%
“…Out of these nine isolates, five could be allocated to the phylogenetic groups B2 and D (noncommensal (Sidhu et al, 2013;Chen et al, 2011;Hamilton et al, 2010;Koczura et al, 2013). Antibiotic resistant shiga toxin producing E. coli (STEC) and ETEC were detected in surface water samples from River Ganga and River Gomti in India (Ram et al, 2008).…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 99%
See 1 more Smart Citation
“…coli pathotypes such as STEC, EPEC, ETEC, and ExPEC and their associated VGs were selected in this study, as other studies have reported the presence of these pathotypes, originating from sewage and/or animal feces, in environmental water (23,24,25,38,46). Overall, 30 (15%) of 200 isolates from eight tanks were positive for the eaeA gene, which belongs to STEC or EPEC (25). However, none of the isolates was positive for the stx 1 , stx 2 , and hlyA genes.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157:H7 is known to harbor stx 1 , stx 2 , or both toxin genes along with the eaeA gene (9,37,43). All eaeA-positive strains were further tested for the presence of the bfpA (bundle-forming pilus) gene, which indicates whether the strains are EPEC or not (25). None of these strains were positive for the bfpA gene, and therefore these strains can be classified as atypical EPEC (aEPEC), as suggested by Kaper et al (35).…”
Section: Discussionmentioning
confidence: 99%